2016
DOI: 10.1371/journal.ppat.1005605
|View full text |Cite
|
Sign up to set email alerts
|

The SH3BGR/STAT3 Pathway Regulates Cell Migration and Angiogenesis Induced by a Gammaherpesvirus MicroRNA

Abstract: Kaposi’s sarcoma (KS)-associated herpesvirus (KSHV) is a gammaherpesvirus etiologically associated with KS, a highly disseminated angiogenic tumor of hyperproliferative spindle endothelial cells. KSHV encodes 25 mature microRNAs but their roles in KSHV-induced tumor dissemination and angiogenesis remain unknown. Here, we investigated KSHV-encoded miR-K12-6-3p (miR-K6-3p) promotion of endothelial cell migration and angiogenesis, which are the underlying mechanisms of tumor dissemination and angiogenesis. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 89 publications
2
47
0
Order By: Relevance
“…This proper regulation is likely achieved through a mixture of positive and negative regulators. A recent study reported an indirect activation of STAT3 by KSHV-encoded miRNAs (including miR-K6)41. Previously, we tested sixteen KSHV miRNAs in primary endothelial cells and no miRNAs increased STAT3 protein levels15.…”
Section: Discussionmentioning
confidence: 90%
“…This proper regulation is likely achieved through a mixture of positive and negative regulators. A recent study reported an indirect activation of STAT3 by KSHV-encoded miRNAs (including miR-K6)41. Previously, we tested sixteen KSHV miRNAs in primary endothelial cells and no miRNAs increased STAT3 protein levels15.…”
Section: Discussionmentioning
confidence: 90%
“…LANA physically interacts with STAT3 and enhances STAT3 transcriptional activity (44) while vGPCR constitutively activates STAT3 independent of IL-6R (45). Kaposin B and miR-K6–3p activates STAT3 by inducing its phosphorylation and targeting negative regulator SH3BGR, respectively (46, 47). vIL-6 also activates the STAT3 pathway through the gp130 subunit (48).…”
Section: Discussionmentioning
confidence: 99%
“…BAC16‐based mutagenesis has also been employed to several studies of KSHV‐encoded 25 mature miRNAs derived from 12 pre‐miRNAs in viral latency and the development of KSHV‐related malignancies By producing BAC16 miR‐K3 mutant viruses, we previously demonstrated that deletion of miR‐K3 from the KSHV genome attenuated KSHV‐induced cell migration and invasion, and also disrupted KSHV latency and impaired angiogenesis . Similarly, with the deletion of miR‐K6 relying on BAC16, we further found that absence of miR‐K6 disturbed cell invasion, migration, and angiogenesis induced by KSHV…”
Section: Discussionmentioning
confidence: 99%